Application of brain ultrasound in premature infants with brain injury - Liu, Lu (Frontiers in Neurology, 2023)
Brain injury is the main factor affecting the development and prognosis of the nervous system in premature infants. Early diagnosis and treatment are of great significance in reducing mortality and disability and improving the prognosis of premature infants. Craniocerebral ultrasound has become an important medical imaging method for evaluating the brain structure of premature infants due to its advantages of being non-invasive, cheap, simple, and bedside dynamic monitoring since it was applied to neonatal clinical practice. This article reviews the application of brain ultrasound to common brain injuries in premature infants.